Perubahan Kurikulum di Awal Era Reformasi (2004-2006) dan Dampaknya terhadap Pendidikan Nasional - Andina Dea Saffina; Farid Fajar Muzaki; Mikhael Zonasuki Simatupang (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
Before the Reformation Indonesia used the 1994 curriculum. However, after the reform of the 1994 curriculum it was replaced with the 2004 curriculum because the details of the subjects students used in the 1994 curriculum were too many and the teacher and students were less interactive. After the 2004 curriculum was created, details of subjects used by students were made simpler, fewer and teachers with students more interactive. One of the strengths of the 2004 curriculum is that it develops student-centered learning. However, after using the 2004 curriculum there were some weaknesses so they were replaced by the 2006 curriculum (KTSP). According to (Sanjaya, 2011) there are a number of weaknesses in the 2004 curriculum, including among them the teacher did not try to find out students 'abilities earlier, the teacher never taught students' way of thinking, the teacher did not try to obtain feedback. Therefore, the 2004 curriculum was replaced with the 2006 curriculum (KTSP) which was expected to become a curriculum that could improve the quality of Indonesian education